A Survey of Food and Feeding Habits of Synodontis in River Benue Along Mayo Ranewo, Ardo-Kola LGA, Taraba State, Nigeria - Danba Elizabeth Pius; Alexander Faith Adule; Allahnanan Emmanuel (Darul Yasin Al Sys, 2025)
This study examines the food and feeding habits of Synodontis species in River Benue, with emphasis on seasonal dietary variations and overall fish health. Thirty-five specimens were collected from Mayo Ranewo, Ardo-Kola Local Government Area, Taraba State, and analyzed using standard morphometric measurements and gut content examination. Results indicate a predominantly herbivorous diet in the early months (August and October), marked by high intake of stems (43.7% and 48.0%) and seeds (42.1% and 42.6%), with limited consumption of animal matter such as insects and crustaceans. In November and December, a dietary shift occurred, with greater proportions of insects (11.7% and 23.5%) and crustaceans (8.4% and 15.7%) consumed. Stomach fullness was consistently high, with 90–100% of specimens containing food across all months. The length–weight relationship revealed negative allometric growth (b = 0.85; R² = 0.95), while the average condition factor (K ≈ 0.23) suggested generally poor health, potentially due to environmental stress or limited food availability. The findings underscore the adaptive feeding strategies of Synodontis in response to seasonal resource fluctuations and highlight the ecological need to preserve riverine health for sustainable fisheries management.